The Adoption Of Energy Efficiency Practices In Manufacturing Companies In Malaysia - Samsudin, Mohd Nizam (2020)
Categorised as among the many businesses having adverse effects on the environment, manufacturing companies are hard pressed to get their acts together. One of the most effective strategies that the companies can employ to reduce global warming, and thus, climate change, is by being more energy efficient. The research attempts to investigate the relationship between independent variable (innovation, communication channels and company characteristics) and the dependent variable of the manufacturing companies in Malaysia to adopt energy efficiency practices in their respective organisations, and charts the adoption of energy efficiency practices within the companies. Data collection was conducted by using a survey method, with respondents coming from all over Malaysia except Sabah and Sarawak due to geographical and financial factors. The research respondents were selected from Federation of Malaysian Manufacturers (FMM) Directory. A total of 660 questionnaires were distributed and 210 of the questionnaires were returned by the respondents, a response rate of 31.82%. The data were analysed by using standard multiple regression technique, arriving at a number of important findings. The research revealed that there is a significant relationship between innovation, communication channels, company characteristics, and manufacturing companies adoption towards energy efficiency practices. In this manner, this research suggested that the manufacturing companies in Malaysia are ready to take the change towards energy efficiency practices in their work to become environmentally friendly.